Estudo FIBRA Poços de Caldas/MG: associações entre fragilidade, fatores funcionais, cognitivos e psicológicos em idosos comunitários - Patricia de Cassia Carvalho (2015)
This dissertation investigates the associations between fragility profiles, functional, cognitive and psychological factors in the elderly of a population sample. Two studies were developed to achieve this goal. Study 1 analyzed the associations between fragility and cognitive performance, through descriptive statistical analyzes and the Chi-Square test, Mann-Whitney test, Kruskal-Wallis test and logistic regression with Stepwise criterion of variable selection. Study 2 verified the interactions between fragility, functional capacity, cognitive performance, depressive symptoms and subjective well-being, using the theoretical model of the analysis of structural equations through Path Analysis, for manifest variables (Structural Equation Modeling for Manifest Variables ). For the analyzes, the FIBRA Poços de Caldas / MG Study Database (n = 389) was used. Overall, the studies demonstrated that: a) low cognitive performance was related to advancing age, low schooling, and impairment of specific cognitive functions; b) positive associations between fragility and functional factors; fragility and cognitive factors; depressive symptoms and functional factors; depressive symptoms and fragility; and depressive symptoms and satisfaction with life. The results obtained in Study 01 reinforce the hypothesis of shared cause for the etiology of fragility and cognitive deficit, as well as the high association between fragility syndrome and cognitive decline. While the data from Study 02 contribute to the construction and strengthening of a multifactorial model of fragility. It is suggested that further studies be carried out to continue the discussion of the issues raised in this research.